LKPD Based on Phenomenon Based Learning (Phenobl) for Mastery of 21st Century Skills on the Material of Colligative Properties of Solutions for Class XII SMA/MA Equivalent - Abdullah, Abdullah; Rasmiwetti, Rasmiwetti; Rahmi, Ainul (LAVOISIER: Chemistry Education Journal, 2024)
Learning is an effort to provide stimulation, guidance, direction, and encouragement to students so that the learning process occurs which is characterized by changes in student behavior as a result of student interaction with the environment. The observation results explained that the 21st century skills possessed by students were still low. One of the causes of low 21st century skills possessed by students is the lack of active involvement of students in the learning process and the lack of orienting phenomena related to chemical concepts. Therefore, to develop 21st century skills, a learner-centered learning model such as Phenomenon based learning model is needed. This research is a development research using the 4-D model. The research aims to produce LKPD based on phenomenon based learning on colligative properties material. The results of e-module validation by material and media validators are considered very valid in terms of content feasibility, presentation aspects, linguistic aspects, graphical aspects, aspects of phenomenon-based learning characteristics, display aspects, and software utilization aspects with a percentage of 100%, 97.5%, 91.67%, 100%, 82.5%, 94% and 100% respectively. This LKPD is in the very valid range with a score of 94.74%, so this LKPD has been confirmed valid and can be tested.